The Comparison of Tnf α (Tumor Necrosis Factor α) Serum Levels Between Cytotoxin - Associated Gene A (Caga) Positive and Negative in Patients with Gastritis Helicobacter pylori - Fitri Armanti Karo; Leonardo Basa Dairi; Gontar Alamsyah Siregar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Background: Helicobacter pylori (H. pylori) infection is the common cause of chronic gastritis in the world that is around 80% in addition to other causes such as autoimmune diseases, drugs, idiopathic and others. The pathogenesis of H. pylori associated with virulence factors consisting of cytotoxin - associated gene A (CagA) and vacuolating cytotoxin A (Vaca). In the case of gastritis occurred acute and chronic inflammatory responses and activation cytokines that cause inflammation of mucous which TNF-α levels increased in patients gatritis H. pylori. Levels of serum TNF-α was found higher in patients infected with H. pylori with CagA positive. The purpose of this study is to investigate the comparison between TNF-α serum level in H. pylori gastritis patients with Cag A (+) and CagA (-).Method: The study was conducted with a cross-sectional design in 30 patients with dyspepsia, using PADYQ score. We performed gastroscopy, biopsy, and CLO test to prove the existence of H. pylori. Furthermore, we used PCR to assess CagA (+) and CagA (-), and ELISA method to measure TNF-α serum level.Results: From 30 subjects, 18 men (60%), 12 women (40%), and the mean age was 53.5 years, the majority of the ethnic was Bataknese  (53.3%), patients with H. pylori gastritis with CagA (+) were 21 (70%) and patients with H. pylori gastritis with CagA (-) were 9 (30%). We found the mean serum levels of TNF-α was higher (3.48) in H. pylori gastritis with CagA (+) than the CagA (-) (1.29) with p value was 0.001.Conclusion: We found increased serum levels of TNF-α in patients with CagA (+) compared to Cag A (-) H. pylori gastritis.